Contemporary Human Capital Issues and Challenges at Modern Workplace - Conceptual Framework: A study - Mariasavery, Lucas; Rajamohan, S. (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2020)
Managing people at workplace are always complex. To manage people has always been tricky with practical problems and everyday issues. The fourth Industrial revolution and the digital age has added still further complexities to human capital management and development. The most complexities and issues are related with social media, emphasis and persistence of latest technological up gradation and the remoteness’ of the new workplace culture. All these make Human Capital which is a difficult job facing lots of challenges and issues. In this context, this conceptual framework research Article is aiming at discussing on the recent issues and challenges that disrupts the human capital functions at workplace with the support of the literature reviews. Therefore identifying, and overcoming HC challenges are the time investment, financial capital, strategic efforts, apart from considering the greatest asset are employees of the organization. The conceptual and theoretical are formed to examine and discuss the emerging issues and challenges of HC management in this modern contemporary context.